Implementation Level of Teaching Factory in Vocational High Schools in West Java, Indonesia - Daryanto, Daryanto; Soeprijanto, Soeprijanto; Nursyahied, Imam; Wahyu Nugroho, Setiadi Dwi; Salsabina, Desti Aulia; Fadillah, Shinta (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the implementation level of the Teaching Factory (Tefa), identify major challenges, and recommend strategies for its development in vocational high schools in West Java, Indonesia. Teaching Factory is an innovation in vocational education that integrates learning with real production practices based on industry standards. Using a descriptive survey with a mixed-methods approach, this research involved 50 selected SMKs and 200 respondents, including principals, teachers, and students. Data were collected through questionnaires, interviews, field observations, and document analysis. The results show that 20% of schools have fully implemented Tefa, 50% are in partial implementation, 20% are in the early stages, and 10% have not implemented it at all. Key challenges include limited facilities (80%), insufficient operational funding (70%), weak industry partnerships (65%), and low teacher competence in managing production-based learning (50%). Some schools also reported difficulties integrating Tefa into the curriculum due to administrative constraints. Despite these challenges, several success factors were identified: strong school leadership, BLUD status for financial flexibility, collaboration with industry partners, teacher innovation, and use of digital tools. Best practices include structured Tefa management, real project integration into learning, and online product marketing.In conclusion, Teaching Factory has strong potential to improve vocational education quality and relevance. Strategic support is needed to scale successful models, improve infrastructure, train teachers, and strengthen industry-school partnerships. The findings serve as a useful reference for policymakers and vocational education stakeholders.